Neuropolitics : thinking, culture, speed - Connolly, William E. (Theory out of bounds ;, 2002)
By taking up recent research in neuroscience to explore the way brain activity is influenced by cultural conditions and stimuli such as film technique, Connolly is able to fashion a new perspective on our attempts to negotiateand thrivewithin a deeply pluralized society whose culture and economy continue to quicken.